A study on common building defects occurred in students college due to wear and tear / Nik Luqman Hakim Mohd Hanipa and Mohd Asrul Hassin - Mohd Hanipa, Nik Luqman Hakim; Hassin, Mohd Asrul (2018)
The purpose of this paper is to explore the common building defects due to wear and tear in student’s college, to identify the common building defects due to wear and tear in student’s college and the last one is to categorized the common building defects due to wear and tear in student’s college. The methodology used in this study is quantitative, consists of scaled questionnaires in obtaining the background information on the commons building defect due wear and tear. The questionnaire which consists of the listed conditions checklist were carried out at two students’ colleges in UiTM Perak; i.e. Kolej Pasir Salak and Kolej Indera Sakti. After the completion of data collection, analysis was performed using two different computer packages: Statistical Package for the Social Sciences and Microsoft Excel Windows. Mean distribution was used to calculate the average degree of defects in the buildings. The result has showed that the highest rank of defects is scuffed on wall, followed by loose doorknob and water stain on the ceiling. Other than that, there are 50 defects that were ranked as considerably occurred and mostly occurred, and ten defects were ranked as less occurred or slightly occurred.